(3TQM HOjYI YGFTI GdHGYhfis - (3Ce YHO GdhgGH YGFTI HfJ jhSa Hf CMeO Hf fGUQ GdHGYhfis; (3YGFTI HfJ jhSa Hf CMeO Hf fGUQ GdHGYhfj, Ce YHO GdhgGH,J (B922 (3g` s
(3ChdgG (B:s
(3hHYO agPg bUjOI UGOQI Yf PGJ bfGYgG , TGgOI HSdGeI GdWHGY dYGFTI GdYGFTI ai QMeI Gddg s
(3BNQgG (B:s
(3hai gPG GdJdhjM caGjg ai GdOdGdI Ydi UMI gPG GdfhY ai HjJgG GdebOe hHGddg GdJhajb s
(3GdHOjYg hGdTQM dgGs
(3fbdJ Yf fSNI LOJgG fSNI GdeUfaI hHChdgG Jedc HJGQjN (B1188(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B241 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B57s
Keywords: (3GdCOHs